(untitled) (Research, Society and Development, 2021)
To know the perception of the nursing team about the Therapeutic Toy (BT) in nursing care in pediatric hospitalization. Descriptive, qualitative study, carried out at the Pediatric Clinic of a University Hospital, in northeastern Brazil. 19 professionals from the nursing team were interviewed, from September to December 2019 and the statements seen according to the content analysis. Nursing professionals were sensitive to the negative aspects of pediatric hospitalization and recognize the importance of means to reduce this suffering, and point out that the use of toys is significant. However, when asked about the resource of BT in the care process, the perception differs from that of its purpose and types. Professionals are still unaware of the legislation regarding BT, but when sharing in their speeches experiences of care, it appears that some practices are close to the purposes of BT. The use of therapeutic toys in the hospital is still seen as dissociated from nursing care, showing the need for studies on the theme and training and sensitization for professionals, promoting critical reflection on the practice of the nursing team in face of this technology in health.